y+12=2(y-12)

Simple and best practice solution for y+12=2(y-12) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for y+12=2(y-12) equation:


Simplifying
y + 12 = 2(y + -12)

Reorder the terms:
12 + y = 2(y + -12)

Reorder the terms:
12 + y = 2(-12 + y)
12 + y = (-12 * 2 + y * 2)
12 + y = (-24 + 2y)

Solving
12 + y = -24 + 2y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-2y' to each side of the equation.
12 + y + -2y = -24 + 2y + -2y

Combine like terms: y + -2y = -1y
12 + -1y = -24 + 2y + -2y

Combine like terms: 2y + -2y = 0
12 + -1y = -24 + 0
12 + -1y = -24

Add '-12' to each side of the equation.
12 + -12 + -1y = -24 + -12

Combine like terms: 12 + -12 = 0
0 + -1y = -24 + -12
-1y = -24 + -12

Combine like terms: -24 + -12 = -36
-1y = -36

Divide each side by '-1'.
y = 36

Simplifying
y = 36

See similar equations:

| 11=8+3r | | 4x+35=151 | | 30=p-(-13) | | x^2+8x+16=40 | | 20=3z+5 | | 157k-19c= | | 3a-1+4a=92 | | 30=p-8+8 | | 2(x+3)=2+6 | | 83+x=129 | | 10x1/5x | | 4+4u=12 | | 5-3x=-14-3x | | 9x+10=12x-14 | | 5(6x+10)=-20 | | -16=-8+n | | 11n-15-10n-14=4 | | 83-x=129 | | 2+3a=32 | | 8x+8b=5b-2x | | 12+x=2001 | | -3x=4y-6 | | p^5q^9/(pq)^3 | | 2x+41=99 | | -a+4=20 | | 8-9r=-19 | | 4x=4+2 | | -6=-2(-4+m) | | 8-7u=-13 | | 105+3x+2x=180 | | w+6=12 | | 22=2-4b |

Equations solver categories